2020
DOI: 10.1108/dat-02-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

From “Codeine Diet” to “Gutter Water”: polydrug use among Nigerian young adults

Abstract: Purpose The purpose of this paper is to explore polydrug use and the factors that motivate the use of multiple substances among selected young adults. Design/methodology/approach A total of 23 male and female participants (aged 23-29 years) who use illicit drugs and prescription pharmaceuticals for non-medical purposes were recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…However, illegal brands containing stronger dosages ranging from 120mg to 250mg are locally produced, imported, and trafficked across most West African states (UNODC, 2021b). A similar increasing trend in the non-medical use of codeinebased cough syrups has also been observed in the country (Dumbili et al, 2020). Cough syrups with codeine are commonly used in the treatment of coughs.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…However, illegal brands containing stronger dosages ranging from 120mg to 250mg are locally produced, imported, and trafficked across most West African states (UNODC, 2021b). A similar increasing trend in the non-medical use of codeinebased cough syrups has also been observed in the country (Dumbili et al, 2020). Cough syrups with codeine are commonly used in the treatment of coughs.…”
Section: Introductionsupporting
confidence: 65%
“…Enhancing physical performance at work was a common motive reported for NMU of tramadol across the qualitative studies (Dumbili et al, 2020;Madukwe & Klein, 2020;Nelson & Alichie, 2022;Olley et al, 2019;Owonikoko et al, 2021). Although tramadol is an opioid with sedative effects, the studies reported that it was seen to be a body enhancing drug with a stimulant-like effect that is useful for increasing an individual's productivity and sustaining physical activities.…”
Section: Motivation For Non-medical Use Of Prescription Opioidsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Southeast Nigeria, Dumbili et al [3] reported that young adult interviewees (University undergraduates and graduates) used Gutter-Water (a cocktail of tramadol, cannabis, codeine, and vodka) and Monkey-Tail (a cocktail of locally-produced gin, cannabis seeds, leaves, stems, and roots). The study also revealed the use of a mixture of 'La Casera Apple Drink (carbonated soft drink) and 'Tom-Tom' (menthol-flavoured candy) to get high (Lacatomtom) [4]. According to Dumbili et al [3], the motivations for taking these substances include heightening and prolonging intoxication and pleasure.…”
Section: Introductionmentioning
confidence: 97%